The Effect of Diabetes Mellitus Foot Exercises on the Stability of Blood Sugar Levels in Patients with Diabetes Mellitus: A Literature Review - Putri Intan Miladiana; Fahrun Nur Rosyid (GLOBAL HEALTH SCIENCE GROUP, 2024)
Diabetes is a degenerative disease that has special characteristics, namely hyperglycemia due to abnormal insulin secretion and suboptimal insulin performance or both. Treatment measures taken by health/medical personnel include: pharmacological treatments such as administering drugs and non-pharmacological treatments such as routine metabolic control, vascular control, ulcer evaluation, foot care and other exercise measures such as foot exercises. Objective: of this study was to apply diabetic foot exercise therapy to reduce blood sugar levels in patients with diabetes mellitus Method: uses a literature review method through a data search base through search engines such as PubMed, Croseff and Google Scholar, with keywords namely: